Badania marketingowe zachowań konsumentów na rynku turystycznym - metodologia, specyfika, zastosowanie - Jedlińska, Maja (Marketing Research of Consumer Behaviour at the Tourist Market - Methodology, Specific Nature, Application, 2006)
Having studied literature and research articles on consumer behavior, one may notice an extensive gap resulting from the lack of such research related to tourist traffic. However, this research turns out to be important due to at least two reasons: complex nature of decisions taken up in case of participation in tourism as well as the scale of opportunities which occur before tourists. In research on future and present tourists' behaviour one should apply mainly qualitative methods and implement their results according to the needs of economic practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 439-446